âPENGARUH KEADILAN, SISTEM PERPAJAKAN, DAN DISKRIMINASI TERHADAP PERSEPSI WAJIB PAJAK MENGENAI ETIKA PENGGELAPAN PAJAK (TAX EVASION)â - , Wahyu Suminarsasi, SE., Dr. Supriyadi, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study examines the influence of fairness, tax system, and discrimination on ethical perceptions of taxpayer about tax evasion in Indonesia specially in Daerah Istimewa Yogyakarta. This study use survey method, with personal income taxpayer in Daerah Istimewa Yogyakarta as a respondents. The results of this study indicate that the tax system has positive associated with perceptions of ethical taxpayer, and discrimination has negative associated with perceptions of ethical taxpayer. While justice has positive associated with ethical perceptions of taxpayer can not be proved.